The Energy Efficient Cities Initiative Practitioners' Roundtable - Energy Sector Management Assistance Program (World Bank, Washington, DC, 2013)
Cities represent a major contributor of greenhouse gas (GHG) emissions. According to the United Nations Population Fund,1 half of the world's population now lives in cities and is responsible for 75% of global energy use and GHG emissions. Since the world's population will continue to grow, and rapid urbanization will continue particularly in the developing world, tackling climate change issues in the urban context will be essential. In response to these challenges, the World Bank's Energy Sector Management Assistance Program (ESMAP), in cooperation with the Bank?s Finance Economics and Urban Department (FEU), has launched an Energy Efficient Cities Initiative, which is designed to help mainstream and scale-up sustainable energy and climate change mitigation actions and investments in the urban context. The first activity proposed under this Initiative is the Energy Efficient Cities Practitioners Roundtable, a facilitated discussion cohosted by ESMAP and FEU. The purpose of this event was to bring together client cities and partner organizations to investigate ongoing initiatives and programs to support cities' sustainable energy goals needs and develop an Energy Efficient Cities Action Plan that will outline a vision and subsequent actions to be taken under the Initiative. The event took place at the Washington DC offices of the World Bank, from October 20-21, 2008.